A comparison of Korean and US continuous improvement projects. Issue 4 (8th April 2014) - Woong Jin, Hyun; L. Doolen, Toni
Abstract : Purpose: – Quality Circles and Kaizen Events have resulted in productivity and quality improvements for organizations. There is limited empirical research comparing these two approaches. This research study was designed to understand the similarities and differences in the structure and outcomes of these two popular continuous improvement approaches in Korea and the USA. The paper aims to discuss these issues. Design/methodology/approach: – A logic model was used to structure a comparative analysis of Quality Circles and Kaizen Events undertaken in six different organizations in Korea and the USA. A logic model framework consisting of four areas (resources, activities, outputs and outcomes) was used to assess the key components of these six improvement projects. Data for three different comparative case study project pairs were collected. Projects were matched on both manufacturer-level and project-level characteristics. Matched projects were similar in size and type of product produced. Findings: – Similarities between Quality Circles and Kaizen Events were identified in every component of the logic model. Both mechanisms were effective in driving improvements in performance and in motivating employees, even though significant differences in the project size, type, and industrial sector existed across the six different projects. Originality/value: – There was no evidence to support the conclusion that one continuous improvement approach is more or less effective than the other. Both approaches produced improvements in both technical and social system outcomes. Overall, it appears based on this study, that both Quality Circles and Kaizen Events can be successfully deployed in an organization's continuous improvement journey.